An Update From the Pediatric Proton Consortium Registry - Hess, Clayton B.; Indelicato, Daniel J.; Paulino, Arnold C.; Hartsell, William F.; Hill-Kayser, Christine E.; Perkins, Stephanie M.; Mahajan, Anita; Laack, Nadia N.; Ermoian, Ralph P.; Chang, Andrew L.; Wolden, Suzanne L.; Mangona, Victor S.; et al. (Frontiers in Oncology, 2018)
Background/Objectives: The Pediatric Proton Consortium Registry (PPCR) was established to expedite proton outcomes research in the pediatric population requiring radiotherapy. Here we introduce the PPCR as a resource to the oncology community and provide an overview of the data available for further study and collaboration. Design/Methods: A multi-institutional registry of integrated clinical, dosimetric, radiographic, and patient-reported data for patients undergoing proton radiation therapy was conceived in May 2010. Massachusetts General Hospital began enrollment in July of 2012. Subsequently, 12 other institutions joined the PPCR and activated patient accrual, with the latest joining in 2017. An optional patient reported Quality of Life (QoL) survey is currently implemented at 6 institutions. Baseline health status, symptoms, medications, neurocognitive status, audiogram findings, and neuroendocrine testing are collected. Treatment details of surgery, chemotherapy and radiation therapy are documented and radiation plans are archived. Follow up is collected annually. Data was analyzed September 25, 2017. Results: A total of 1,854 patients have consented and enrolled in the PPCR from October 2012 until September 2017. The cohort is 55% male, 70% Caucasian, and comprised of 79% United States residents. Central nervous system (CNS tumors comprise 61% of the cohort. The most common CNS histologies are: medulloblastoma (n 276), ependymoma (214), glioma/astrocytoma (195), craniopharyngioma (153), and germ cell tumors (108). The most common non-CNS tumors diagnoses are: rhabdomyosarcoma (191), Ewing sarcoma (105), Hodgkin lymphoma (66), and neuroblastoma (55). The median follow up is 1.5 years with a range of 0.14 to 4.6 years. Conclusion: A large prospectively-followed population of children irradiated with proton therapy has reached a critical milestone to facilitate long-awaited clinical outcomes research in the modern era. This is an important resource for investigators both in the consortium and for those who wish to access the data for academic research pursuits.